A context-aware meeting alert using semantic web and rule technology. (21st March 2008) - Antoniou, Grigoris; Bikakis, Antonis; Karamolegou, Anna; Papachristodoulou, Nikos; , Manolis Stratakis
This paper describes a context-aware meeting alert, which aims at alerting the user in time about upcoming scheduled calendar events, considering the state of the user's context. This application integrates semantic web technology in RDF (for representing calendars), semantic web rules (for making a context dependent decision about the precise timing of the alert), and mobile technology for location sensing and message delivery. The outlined work is an experiment seeking to demonstrate the feasibility of applying efficient, semantically sound semantic web reasoning to mobile applications.